Trust in leadership and organizational justice as factors that influence innovative behavior in organizations on an ongoing basis - Wahyutomo, Dito; Permatasari, Evi (Inovbiz: Jurnal Inovasi Bisnis, 2024)
The purpose of this study was to test and analyze the effect of trust in leadership and organizational justice on innovative behavior. this research uses a quantitative approach, the data is obtained using questionnaire techniques. Respondents in this study amounted to 120 employees of foreign investment companies in Malang District. this study has two hypotheses with the analysis test using SEM PLS 4.0. the results of the analysis test in this study. the first hypothesis can be seen that trust in leadership has a significant effect on innovative behavior.The second hypothesis is that organizational justice has a significant effect on innovative behavior.